IMPLEMENTASI ADAT DAN SYARAK PADA TINGGALAN ARKEOLOGIS DI SURAU NGALAU NAGARI BALIMBIANG TANAH DATAR - Syahrul Rahmat; Muhammad Ikbal (Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2022)
Minangkabau has a famous traditional adage adat basandi sayarak, syarak basandi kitabullah or the norms of Minangkabau customary law (Adat) depends on Moslem law (Shariat), and shariat depends on Al-Qur’an (Islamic holy book). The realization of adat and shariat have been found in tangible and intangible legacies. Surau Ngalau (prayer house or small mosque) along with archeological remains inside it are evidences of adat and shariat actually worked hand-in-hand. In terms of non-physic legacy, religious activities in Surau Ngalau lead to Tarekat Syatariyah lasted until the early 20th century AD. The study adopted historical research and archeological research to investigate the development of Tarekat Syatariyah in Nagari Balimbiang, Tanah Datar as well a the interaction between adat and religion realized in prayer house building and its remains artifacts. The findings reveal that the implementation of adat and shariat has existed for a long time supported by the existence of Surau Ngalau and artifacts such as keris (traditional small sword) and carano found inside it.